A high performance Ge/Si0.5Ge0.5/Si heterojunction dual sources tunneling transistor with a U-shaped channel. (June 2017) - Li, Wei; Liu, Hongxia; Wang, Shulong; Wang, Qianqiong; Chen, Shupeng
Abstract: In this paper, a new Ge/Si0.5 Ge0.5 /Si heterojunction dual sources tunneling transistor with a U-shaped channel (Ge_DUTFET) is proposed and investigated by Silvaco-Atlas simulation. The line tunneling perpendicular to channel and point tunneling parallel to channel simultaneously occur on both sides of the gate. The Ge is chosen as the source region material to increase the line tunneling current. The designed heterojunction between the Ge source and Si channel decreases the point tunneling barrier width to enhance the point tunneling current. And this heterojunction can also promote the Ge_DUTFET to occur point tunneling at the small gate voltage, which makes it obtain the smaller turn-on voltage. Furthermore, the Si0.5 Ge0.5 buffer layer is also helpful for the enhancement of performance. The simulation results reveal that Ge_DUTFET has the better performance compared with the Si_DUTFET. The on-state current and average subthreshold swing of Ge_DUTFET are 1.11 × 10 −5 A/μm and 35.1mV/dec respectively. The max cut-off frequency ( f T ) and gain bandwidth product (GBW) are 26.6 GHz and 16.6 GHz respectively. The f T and GBW of the Ge_DUTFET are respectively increased by ∼27.4% and ∼84.3% compared with the Si_DUTFET. Highlights: A Ge/Si0.5 Ge0.5 /Si heterojunction dual sources UTFET (Ge_DUTFET) is designed. The point tunneling and line tunneling simultaneously occur on both sides of gate. The Ge_DUTFET has the higher on-state current, f T and GBW. The Ge_DUTFET has smaller turn-on voltage. Ge_DUTFET has the better analog/RF performance compared with the Si_DUTFET.